Technology spillover from foreign direct investment in Turkey - Özcan Karahan (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2016)
Purpose - The aim of this paper is to investigate the relationship between Foreign Direct Investment flows and economic growth using quarterly data for the period of 2002 and 2015 in Turkey. Thus we try to examine whether technological diffusion generated by FDI inflows to Turkey enhances the innovative capability of the country or not. Design/methodology/approach - The variables Foreign Direct Investment (FDI) and Gross Domestic Product (GDP) are sourced from Electronic Data Delivery System (EDDS) in Central Bank of the Republic of Turkey. FDI series consist of values called 'Net Incurrence of Liabilities' in Balance of Payments Analytical Presentation while GDP series gather from the expenditure based GDP data in EDDS. Both Johansen Cointegration Test and Granger Causality Test are applied to examine between Foreign Direct Investment flows and economic growth in Turkey. Findings - Results reveal that there is not any significant link among the FDI and economic growth during the studied time period in Turkey. It seems that FDI inflows to Turkey is not complementary to economic growth, which shows that positive spillover effect sourced from FDI inflows to Turkey does not exist. Research limitations/implications - Policymakers should recognize that technology spillover effects of FDI do not occur without greater absorptive capacity. Attracting FDI is only one part of the story and thus not yield the desired benefits itself. Positive effects of FDI depends on the overall incentive and capacity structure of the host country. Then the key policy implication here is that policymakers should give same weight of policies aimed at attracting FDI versus those that seek to improve local economic conditions. Originality/value - This study insight the spillover effects of FDI based on Turkish experience that benefits from FDI do not occur automatically and effortlessly in developing countries.
Keywords: F21; F43; O33; 330; Technology Spillover; Foreign Direct Investment; Turkey